Risk Vulnerability and Takaful Acceptance: Evidence from a Frontier Market - Mas'ud, Abdulsalam (International Journal of Economics, Management and Accounting, 2017)
Recently, acceptance of takaful as an Islamic financial product has been declining in African Muslim-dominated countries such as Kenya, Tunisia, and Nigeria. In understanding the causes of this trend and to proffer a possible solution, this study examines the effects of individuals’ attitude toward takaful, perceived behavioral control, individual’s risk vulnerability on takaful acceptance intention in the Nigerian Frontier Market. It also examined the moderating effect of individual’s risk vulnerability on the relationship between attitudes toward takaful, perceived behavioral control, and takaful acceptance intention. Through a quantitative methodology employed for the purpose, the results revealed that attitude toward takaful, perceived behavioral control and individual’s risk vulnerability are significantly related to acceptance intention. Moreover, individual’s risk vulnerability moderates the relationship between attitude toward takaful, perceived behavioral control, and takaful acceptance intention. In line with these findings, theoretical and practical implications, as well as the direction of future research, were highlighted.